PENGARUH KESEJAHTERAAN GURU DAN KEPUASAN KERJA ASPEK FINANSIAL TERHADAP LOYALITAS KERJA GURU DI SMK AL-AMANAH TANGERANG - Najwa Hafana; Munirul Abidin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study was conducted to analyze the impact of teacher welfare and financial job satisfaction on teacher work loyalty at SMK Al-Amanah Tangerang, both partially and simultaneously. A quantitative field research approach was applied, involving the entire teaching staff population totaling 52 subjects at SMK Al-Amanah South Tangerang through a census or saturated sampling technique. Data were gathered using a Likert scale questionnaire and processed using IBM SPSS 25 software, which included multiple linear regression, hypothesis testing (t-test and F-test), and the coefficient of determination (R²). The analysis reveals that partially, neither welfare nor financial job satisfaction exerts a significant effect on work loyalty. However when tested simultaneously, both factors are proven to have a significant combined effect on loyalty, contributing 12.0% to the total variance. The novelty of this research lies in the application of an integrative analytical model that highlights the joint effect of these two variables within a private Islamic foundation-based vocational school (SMK) in the Tangerang region, thereby distinguishing it from previous studies that generally focused on public schools or examined these variables separately.